Mitophagy regulates kidney diseases - Xiaolu Fan; Linlin Wu; Fengqi Wang; Dong Liu; Xufeng Cen; Hongguang Xia (Karger Publishers, 2024)
Background: Mitophagy is a crucial process involved in maintaining cellular homeostasis by selectively eliminating damaged or surplus mitochondria. As the kidney is an organ with a high dynamic metabolic rate and abundant mitochondria, it is particularly crucial to control mitochondrial quality through mitophagy. Dysregulation of mitophagy has been associated with various renal diseases, including acute and chronic kidney diseases, and therefore a better understanding of the links between mitophagy and these diseases may present new opportunities for therapeutic interventions. Summary: Mitophagy plays a pivotal role in the development of kidney diseases. Upregulation and downregulation of mitophagy have been observed in various kidney diseases, such as renal ischemia-reperfusion injury, contrast-induced acute kidney injury, diabetic nephropathy, kidney fibrosis, and several inherited renal diseases. A growing body of research has suggested that PINK1 and Parkin， the main mitophagy regulatory proteins， represent promising potential therapeutic targets for kidney diseases. In this review, we summarize the latest insights into how the progression of renal diseases can be mitigated through the regulation of mitophagy, while highlighting their performance in clinical trials. Key Message: This review comprehensively outlines the mechanisms of mitophagy and its role in numerous kidney diseases. While early research holds promise, most mitophagy-centered therapeutic approaches have yet to reach the clinical application stage.